THERMAL EFFECTS OF THE INTRUSION OF BASALTIC MAGMA INTO A MORE SILICIC MAGMA CHAMBER AND IMPLICATIONS FOR ERUPTION TRIGGERING - Snyder D. (My University, 2000)
Shortly after a basaltic injection invades a more silicic magma chamber, a two-layer convecting system develops. The timescale for the start-up of convection, the rates at which the basaltic magma cools and the silicic magma warms, and the lifespan of a thermal gradient in the silicic magma can all be quantified using a parameterized scaling analysis coupled with the thermodynamics of crystallization. This analysis reveals that the timescale of start-up of convection is less than 1 h for the basaltic layer and days to weeks for the silicic layer, depending on its viscosity. For a given thickness, basaltic layers cool and silicic layers warm at surprisingly constant rates that depend weakly on their relative temperatures. Basalts cool in the order of 5 K day-1 for a thickness of 1 m. Thicker layers take proportionally longer to cool. Except for a thermal boundary region on the order of 1 m thick, silicic magmas only warm if they are less than about 100 times thicker than the basaltic injection. When sufficiently thin, they warm at an averaged rate of the order of 10 K day-1 for a thickness of 1 m. Thicker silicic layers take proportionally longer to warm. A thermal gradient will be induced in the silicic magma that will take years to tens of years to decay per kilometer thickness of silicic magma. These timescales are central to the role of magma commingling in explosive eruption triggering. The time between commingling of basaltic and silicic magmas prior to explosive silicic eruptions is on the order of days to weeks, equivalent to the timescale of forming a thermal boundary layer in the silicic magma (i.e. the start-up time for convection), but short compared to the cooling time of a basaltic replenishment. These timescales support the triggering of explosive eruptions by increased exsolution of volatiles in the silicic magma rather than the basaltic.
Keywords: MAGMA CHAMBERS; THERMAL HISTORY; VOLCANISM; ERUPTIONS; FLUID DYNAMICS